From Stone Age to Stellenbosch: studies on the ancient Near East in honour of Izak (Sakkie) Cornelius - Dijk-Coombes, Renate M. van; Swanepoel, Liani C.; Kotzé, Gideon R. (Ägypten und Altes Testament, 2021)
Intro -- Preface -- Table of Contents -- List of Contributors -- List of Abbreviations -- van Dijk-Coombes / Swanepoel / Kotzé: FROM STONE AGE TO STELLENBOSCH: AN INTRODUCTION TO THE VOLUME -- Schroer: WERE GODDESSES ALREADY WORSHIPPED IN THE EARLY CHALCOLITHIC PERIOD? -- Ikram: A GREAT CAT WALKS SOUTH: A PETROGLYPH FROM KHARGA OASIS (EGYPT) -- van Dijk-Coombes: THE MANY FACES OF ENHEDUANNA'S INANA: LITERARY IMAGES OF INANA AND THE VISUAL CULTURE FROM THE AKKADIAN TO THE OLD BABYLONIAN PERIOD -- Oshima / Gruseke : SHE WALKS IN BEAUTY: AN ICONOGRAPHICAL STUDY OF THE GODDESS IN A NIMBUS -- Frevel: THE MANY FACES OF THE GODDESS: SEKHMET -- Berlejung: ANOTHER FACE OF THE GODDESS: A TERRACOTTA PLAQUE FROM QUBUR AL-WALAYDAH -- Nunn: FRAUENBILDNISSE UND IHRE GESTEN -- Pyschny: FEEDING, NURSING, CARING … : SOME NOTES ON THE WOMAN AND CHILD FIGURINES FROM PERSIAN PERIOD ISRAEL/PALESTINE -- Jonker: A CONFLATION OF DIVINE AND ROYAL IMAGERY? THE CASE OF THE WINGED SYMBOL IN ACHAEMENID PERSIA -- Niehr: DIE BETERSTATUE VON TELL FEKHERIYE ALS DOKUMENT DER KÖNIGSIDEOLOGIE DES HERRSCHERS HADDAYISʿI VON BĪT BAḪIĀNI -- Leuenberger: YAHWEH AND HIS ASHERAH IN THE THREE PITHOI INSCRIPTIONS FROM KUNTILLET ʿAJRUD: A RE-EVALUATION -- de Hulster: THE HORIZONTAL DIMENSION OF THE ANCIENT AND BIBLICAL VIEW OF THE WORLD -- Kotzé: LOOKING AGAIN AT THE NAKEDNESS OF NOAH -- LeMon: CLAPPING AND SHOUTING IN PSALM 47:2 WITH ATTENTION TO THE ICONOGRAPHY OF APPLAUSE -- Slabbert / Swanepoel: FAKE, PSEUDO OR TRUE? CLASSIFYING TWO VOTIVE ANIMAL MUMMIES FROM A SOUTH AFRICAN MUSEUM -- Masters / Noether: SOUTH AFRICA AND THE ANCIENT WORLD: ARTEFACTS AND THEIR USE IN TEACHING AND OUTREACH -- Index of Ancient Sources -- Index of Authors -- Index of Subjects -- Leere Seite.